Advances in Optical Sciences Congress 2009
DOI: 10.1364/ipnra.2009.iwa1
|View full text |Cite
|
Sign up to set email alerts
|

InGaAsP/InP based Flattened Ring Resonators with Etched Beam Splitters

Abstract: A novel flattened ring resonator design utilizing Etched Beam Splitters (EBS) in InGaAsP/InP is purposed and demonstrated. A multiple-thickness hard mask that compensates for RIE-lag realizes waveguides and EBS in a single etch step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…For integrated optics this is seldom the case, thus, a more rigorous approach is needed. So far, most predictions on EBS performance has been done using numerical 2D-FDTD simulations [8][9][10]14]. Some full 3D-FDTD treatment of EBS structure has recently been reported [12,13].…”
Section: Ebs Design and Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…For integrated optics this is seldom the case, thus, a more rigorous approach is needed. So far, most predictions on EBS performance has been done using numerical 2D-FDTD simulations [8][9][10]14]. Some full 3D-FDTD treatment of EBS structure has recently been reported [12,13].…”
Section: Ebs Design and Modelingmentioning
confidence: 99%
“…More recently, the EBS has demonstrated better performance with silicon-on-insulator (SOI) [12], AlGaAs [13] and polymer based waveguide platforms [8]. We have extended to the InP/InGaAsP material system in order to integrate the EBS coupler with an active gain platform [14,15]. Here, we report on the modeling, fabrication and characterization of such EBS couplers in InP/InGaAsP.…”
Section: Introductionmentioning
confidence: 99%
“…The gap in the CGC between two waveguides functions as a half mirror. References [3][4][5] have demonstrated that an air slit could be used as a half mirror or a corner mirror. The fabrication of the CGC is relatively easy because complicated …”
Section: Design Of Cgc DC and Mmi Coupler Structuresmentioning
confidence: 99%